ANALISIS KOMPARASI ANTARA PENGGUNA SISTEM REGISTRASI WEB-BASED DAN NONWEB-BASED DALAM PENERIMAAN INOVASI TEKNOLOGI INFORMASI - Nuhoni Nalurita; Hendrian Hendrian (Jurnal Organisasi Dan Manajemen, 2007)
This research investigated the behavioral differences between web-based registration system?s users and manual registration system?s users. There are several difference characteristics of each user, for instance; Personal Innovativeness in the domain of Information Technology (PIIT), attitude, usefulness, ease of use, subjective norm, behavioral control, facilitating condition, and self efficacy. The samples of this research are university students in Yogyakarta. The result of this research shows that web-based registration system?s users has higher PIIT, higher positive attitude, higher subjective norm, higher behavioral control, higher facilitating condition, and higher self efficacy than manual registration system?s user. There?s no difference between manual registration system?s users and web-based registration system?s users for the usefulness perception and ease of use